A Qualitative Study on the Influencing Factors of E-Government Adoption to Improve Public Trust in Local Government: Case Study of Rokan Hulu Municipality - Fadrial, Rudy; Sujianto; Simanjuntak, Harapan Tua Ricky Freddy; Wirman, Welly (The Indonesian Journal of Computer Science, 2024)
Amidst global public trust challenges, e-government emerges as a promising solution to bolster trust. In Indonesia, rural areas face obstacles hindering effective e-government implementation. This paper explores Rokan Hulu Municipality's initiatives, aiming to understand e-government's impact on public trust at the rural/district level, bridging critical knowledge gaps. This study employs a qualitative approach to investigate the factors influencing e-government adoption. Primary data is gathered through interviews with key stakeholders, supplemented by secondary data from organizational documents. Employing open and axial coding, this study organizes findings to the Technology-Organization-Environment framework. Within the technological dimension, obstacles such as infrastructure; integration and interoperability; data security and confidentiality; and service providers, third parties, or vendors emerge as significant barriers. In the organization dimension, culture, organizational capability, budget constraints, human resource quality, perceptions, bureaucracy, and strategy become challenges, with organizational capability and strategy showing mixed impacts due to incomplete initiatives and limited inter-agency coordination. In environment dimension, digital divide, regulatory availability, and public participation become inhibiting factors, while political intervention becomes the driving factor.